SOMALI PIRATES TAKE TO THE HIGH SEAS: EXPEDIENCY OR LONG-TERM PIRATE STRATEGY? - Fouche, Henri (Scientia Militaria - South African Journal of Military Studies, 2011)
In 2008 the highest number of attacks recorded against ships in the world wasreported to have taken place off the coast of Africa. These attacks were carried out atgreater distances from land, along the east coast of Africa, than ever before. In thisarticle the extent of piracy and armed robbery against ships in the African contextand underlying causes of piracy and armed robbery against ships off the coast ofEast Africa will be presented. The objective is to analyse incidents and the land andsea based causes in East Africa to account for the shift in strategy from attackingships in territorial waters to attacking ships on the high seas. A secondary aim is todetermine, in view of the shifting background to the attacks, the responsibilities ofnavies and other role players in the process of countering such attacks. The articlesuggests that states need to review national legislation related to maritime securityand that all state role players in the maritime domain need to cooperate moreefficiently.